Comparison of pull and catch phases during clean exercise - Hayashi, R.; Kariyama, Y.; Yoshida, T.; Takahashi, K.; Zushi, A.; Zushi, K. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The purpose of this study was to identify differences in kinetic characteristics between the performed the PC at 30%, 60%, and 90% of one repetition maximum. Kinetic data were collected from recorded data by using a Vicon motion system and force platforms. In the comparison between the pull and catch phases, the kinetic characteristics of the catch phase were as follows: 1) The peak ground reaction force did not significantly differ according to load. 2) Ankle and knee kinetics showed large values. 3) The force and power in the ankle and knee did not significantly differ between the light load (30%) and heavy load (90%). Therefore, the importance of using PC in training not only for the pull movement but also for the catch movement.